(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Introduction: Pneumonia is a worldwide, serious threat to health and an enormous socio-economic burden for health care system. According to recent WHO data, each year 3-4 million patients die from pneumonia. The clinical presentations and bacterial agents responsible for community acquired pneumonia (CAP) varies according to geography and culture. Methods: A cross sectional observational study conducted among the 53 consecutive patients with a clinical diagnosis of CAP in admitted patient in the department of Medicine, DMCH, during January 2010 to December 2010. Hematological measurements (TC of WBC, Hb%, ESR, platelet count), blood culture, chest X-ray P/A view, sputum for Gram staining and culture sensitivity, sputum for AFB, blood urea and random blood sugar were done in all cases. ELISA for IgM antibody of Mycoplasma pneumoniae and Chlamydia pneumoniae were done in sputum culture negative cases. Results: The mean (±SD) age was 38.9±17.3 years and Male female ratio was 3:1. Fever, chest pain and productive cough were the most common clinical features. The mean (±SD) respiratory rate was 23.0±2.8 /minute . COPD and DM were found in 17.0% and 5.7% of patients respectively . Blood culture was found positive in only 1.9% of the study patients. Gram positive Cocci 62.26%, Gram negative Bacilli 9.43%, mixed Gram positive cocci and Gram negative bacilli 11.32% and Gram negative Cocco Bacilli 1.9% were observed and in 15.03 % cases, no bacteria could be seen. Sputum culture revealed 53.8% streptococcus pneumoniae, 26.9% Klebsiella pneumonia as predominant organism. Mycoplasma pneumoniae and Chlamydia pneumoniae were found in 7.4% and 3.7% respectively by serological test. For Streptococcus pneumoniae, sensitive antibiotics were Amoxyclav and Levofloxacin. For Gram negative bacilli and coccobacilli, more sensitive antibiotics were Meropenem, Ceftriaxone, and Clarithromycin. The best sensitive drug were found meropenem. The mean (±SD) duration of hospital stay was 5.0±1.7 days with ranging from 3 to 10 days. Conclusion: Region based bacteroiological diagnosis of Cap is important for selecting the best and sensitive drugs for complete cure. J Bangladesh Coll Phys Surg 2016; 34(3): 128-134